2020
DOI: 10.1111/petr.13658
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of treatment strategy of tandem high‐dose chemotherapy and autologous stem cell transplantation in combination with 131I‐MIBG therapy for high‐risk neuroblastoma

Abstract: This study was performed to evaluate the safety and effectiveness of tandem HDCT/ASCT combined with targeted radiotherapy using 131I‐MIBG for high‐risk neuroblastoma. Patients with high‐risk neuroblastoma were treated with 8 to 10 cycles of induction chemotherapy before tandem HDCT/ASCT. Patients received 131I‐MIBG treatment before the second HDCT/ASCT. Local radiotherapy and maintenance therapy were performed after tandem HDCT/ASCT. Between 2012 and 2016, 19 patients were diagnosed with high‐risk neuroblastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
(74 reference statements)
1
18
0
1
Order By: Relevance
“…Hickeson et al showed that 210 lesions were detected on the post-therapy 131 I-mIBG scintigraphy compared with 151 on the 123 I-mIBG scintigraphy in 16 patients (89%) [ 17 ]. For the patients with neuroblastoma without mIBG-avid lesions on diagnostic 123 I-mIBG scintigraphy, post-therapy 131 I-mIBG WBS images detected occult lesions in five of five (100%) [ 13 ] and post-therapy 131 I-mIBG scan with no information about SPECT in three of fifteen (20%) patients [ 5 ]. This study found that the detection rate of 32% in patients without mIBG-avid lesions was less compared to that in most reports on patients with mIBG-avid lesions using 123 I-mIBG scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hickeson et al showed that 210 lesions were detected on the post-therapy 131 I-mIBG scintigraphy compared with 151 on the 123 I-mIBG scintigraphy in 16 patients (89%) [ 17 ]. For the patients with neuroblastoma without mIBG-avid lesions on diagnostic 123 I-mIBG scintigraphy, post-therapy 131 I-mIBG WBS images detected occult lesions in five of five (100%) [ 13 ] and post-therapy 131 I-mIBG scan with no information about SPECT in three of fifteen (20%) patients [ 5 ]. This study found that the detection rate of 32% in patients without mIBG-avid lesions was less compared to that in most reports on patients with mIBG-avid lesions using 123 I-mIBG scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…123 I-meta-iodobenzylguanidine ( 123 I-mIBG) scintigraphy has been used for evaluating disease extent in children with neuroblastoma, and 131 I-mIBG therapy has been used for children with high-risk neuroblastoma and mIBG-avid lesions [ 1 , 2 , 3 ]. Consolidation therapy incorporating high-dose 131 I-mIBG has yielded good overall and event-free survival in children with high-risk neuroblastoma with complete response (CR) to primary therapy as demonstrated by diagnostic 123 I-mIBG scintigraphy [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post MIBG therapy whole body scan in high-risk neuroblastoma patients may reveal hidden mIBG-avid lesions, which are under the level of detection by diagnostic 123I-MIBG images (27)(28)(29). The fact, that in 13 patients the MIBG uptake was absent can be explained by a time interval between the qualification and administration of the therapy, during which patients received chemotherapy.…”
Section: Adverse Effects and Second Malignanciesmentioning
confidence: 99%
“…The authors reported an overall survival of 83% after five years. Of note, no treatment-related mortality was registered [15]. High dose 131 I-MIBG targeted therapy has been applied recently in Japan to treat children with relapsed neuroblastoma, who were administered with treatment ranging from 444 to 666 MBq/kg.…”
Section: Metaiodobenzylguanidine (Mibg)mentioning
confidence: 99%